"The Chief Characteristical Mark of the True Church": John Locke's Theology of Toleration and His Case for Civil Religion. Issue 2 (24th April 2014) - Herold, Aaron L.
Abstract This essay argues that Locke's Reasonableness of Christianity provides a morally robust argument for religious pluralism—one which avoids the pitfalls of relativism and official neutrality by elucidating the need for a civil religion of toleration. The work thus contains Locke's friendly critique of his more radical Enlightenment contemporaries who had openly debunked the Bible. This critique is friendly, I argue, because Locke ultimately agrees with Spinoza and Hobbes about revelation, miracles, and religion's psychological causes. While Locke joined these thinkers in a common project to make Christianity less sacrificial and friendlier to enlightened selfishness, his analysis also reveals the need to retain some of its self-abnegating spirit in liberalism's service. But Locke has difficulty accounting for that spirit itself, and this problem in one of liberalism's original theorists may help explain the dissatisfactions and anxieties troubling tolerant societies today.